2017
DOI: 10.21608/ejh.2017.5686
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet rich plasma enhances satellite cells expression of MyoD and exerts angiogenic and antifibrotic effects in experimental rat model of traumatic skeletal muscle injury

Abstract: Introduction: Skeletal muscle injuries comprise the greater part of sports-related injuries. Role of growth factors in healing of injured tissue encouraged the use of platelet-rich plasma (PRP). Aim of the work: We aimed to study the effect of PRP on skeletal muscle injury. Materials & Methods: Forty adult male rats were divided into four equal groups; control and 2, 7, 14 days after the injury. The injured muscles were either treated with PRP or left without treatment. The rats were sacrificed and the muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This process is regulated by a selective apoptosis process that occurs simultaneously with the maturation of new blood vessels. Apoptosis refers to the automatic and programmed death of normal cells [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…This process is regulated by a selective apoptosis process that occurs simultaneously with the maturation of new blood vessels. Apoptosis refers to the automatic and programmed death of normal cells [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, there was preservation of vasculature; capillaries luminal areas, ECs and pericytes that was confirmed by the significant increase in CD34 positive ECs. Former studies have proved the angiogenesis effect of PRP in different tissues; lung injury [59] and traumatic skeletal muscle injury where a significant increase in CD34 immunopositive ECs lining newly formed capillaries after PRP treatment was found [60] . Blood vessels do not only convey oxygen and nutrients; they also provide informative signals to the surrounding microenvironment, thus, angiogenesis is fundamental in tissue regeneration and its targeting is good policy to regenerate damaged or lost tissues [59] .…”
Section: Discussionmentioning
confidence: 99%
“…Different researches [9,11,13,44] found that PRP has an antifibrotic effect as it contains antifibrotic molecules, growth factors, and serum amyloid protein which could ameliorate the fibrosis. Additionally, PRP treatment increases muscle regeneration by stimulating myogenesis [47,48] . Also, it had antiapoptotic effect by downregulating the expression of apoptotic genes as DAPK1 and BIM mRNA and inhibiting p53, Bax, and caspase-3 levels [9] .…”
Section: Discussionmentioning
confidence: 99%